Otentisitas Konsep al-Murâbahah Di Bank Syariah - Suprihatin Suprihatin (Universitas Islam Negeri Jakarta, 2015)
The aim of this research is to returning the authenticity of al-murâbahah in syariah bank. The method of this research is qualitative library method with symbolism interaction approach. The problem of this research is an unauthenticity of al-murâbahah in syariah bank because there is no trading. Al-murâbahah in syariah bank was operated base on funding. So that al-murâbahah in syariah bank can be called unauthentic. The urgency to returning the authenticity of al-murâbahah is to obey the syariah, to make someone who operated al-murâbahah in syariah bank did’n have a split of thinking, to built a correspondence thruth and coherence thruth in Islamic civilization.DOI: 10.15408/ajis.v15i1.2850